Multiplex PCR assay for detection of Helicobacter pylori isolated from Iraqi dyspeptic patients - Kalaf, Elham A. (Iraqi Journal of Cancer and Medical Genetics, 2013)
Helicobacter pylori (H. pylori) is one of the most common infections worldwide and is associated with gastric disorders. H. pylori is genetically unstable and this reflected on its virulence factors and type of diseases. Cytotoxin associated gene A (CagA) product is a major virulence factor is thought to be associated with gastric disease. It is injected into epithelial cells, undergoes phosphorylation by host cell kinases, and perturbs host signaling pathways. In the present study, we used multiplex PCR assay for rapid detection of H. pylori infection and for the determination of CagA genotypes directly from gastric biopsy specimens. Gastric biopsies were collected from 210 patients with dyspeptic symptoms. Genotypic analysis of H. pylori genes was found 91.17% for 16S rRNA, 87.25% for flagellin A, 89.21% for glmM (ureC) and cagA gene was detected in (39.21%) 40 biopsy specimens. Our study indicated that ureC (glmM) gene PCR is the most specific for the detection of H. pylori in gastric biopsy specimens compared with16S rRNA gene. There were significant differences (P ≤ 0.01) in cagA positive rate, among different diseases.